Open Universities and Open Educational Practices: A Content Analysis of Open University Websites - DeVries, Irwin (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2019)
The purpose of this study is to provide an overview of how open universities depict their current institutional engagement in open educational practices. In view of the growth of programming for non-traditional students by conventional universities, particularly through online learning and increasing interest in open educational practices, the intention is to gain a better understanding of the unique contributions currently made, or potentially to be made, by open universities in comparison to conventional universities. The study is conducted through a content analysis of open university websites, exploring key themes related to access-oriented open educational practices derived from terms and related concepts in relevant literature. With the growth of distance education, online learning, and other emerging access-oriented open educational practices in traditional higher education, open universities should be uniquely situated to provide visible leadership in these domains. The open university website content analysis explores the extent to which this is the case.